Literacy Virtual Entrepreneur in Indonesia - Tindas, Arnold; Sumarlin, Suryadi; ., Sasmoko; B Oentoro, Jimmy; Indrianti, Yasinta (International Journal of Engineering and Technology, 2018)
The potential strength of entrepreneurship in Indonesia lies in the potential of human resources who are a literate internet. Nevertheless, there are still some weaknesses that are not yet equal to the ability. The problem is how is the condition of Indonesian entrepreneur about its virtual literacy? Construct Validity uses the Item Response Theory (IRT) approach through Orthogonal Iteration. The reason, because all dimensions and indicators are the results of the theoretical studies are called as signs of the variables Literacy Virtual Entrepreneur Indonesia (Y). The number of samples of the instrument test was 81 entrepreneurs consisting of 27 districts/cities each represented 3 entrepreneurs. The R-criteria of the Product Moment is set at 0.221. Of the 32 items planned, proved to be all valid. The reliability of "valid instrument" of the Virtual Literacy variables of Entrepreneur Indonesia (Y) as internal consistency is calculated by Cronbach Alpha formula, the result is 0.892. Research methods with Neuroresearch. The result of the research: Firstly, Indonesian entrepreneurs tend to be significantly virtual literate on Î± <0,05. Second, having the capacity to realize information technology literacy (X4) is the most powerful indicator to realize the formation of Literacy Virtual Entrepreneur Indonesia (Y). It is able to determine an increase of 83,521 times from the condition of Literacy Virtual Entrepreneur Indonesia (Y).Â Â